Attitudes towards women in the military and their relation to both quantity and quality contact with female leaders - Nicol, Adelheid A. M.; Mayrand Nicol, Amélie (Frontiers in Psychology, 2024)
The military values many stereotypical male qualities such as power, dominance, aggression, and physical strength. Due to these stereotypically male-associated values, women occupy fewer leadership positions in the military than men and can be targets of sexual harassment. Investigating factors that influence attitudes towards women in the military can provide guidance for a change in military culture. Reducing prejudice can be done by creating contact experiences with minority group members. Creating contact experiences to reduce prejudice towards women has received limited attention as women are typically not considered minority group members. However, in a military context where women represent a minority of the workforce, contact theory may be applied. We provide empirical support for the importance of experiencing contact with women in leadership positions by studying whether it is related to attitudes towards women being in the military. In both military and civilian samples we also examine whether intergroup anxiety, perspective-taking, and empathy are important for favorable attitudes towards women in the military.